2015
DOI: 10.4236/lce.2015.62005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Information Provision on Pro-Environmental Behaviors

Abstract: To reduce the environmental load of the household sector, it is important to enhance people's proenvironmental behaviors (PEBs). Information provision has been considered as one of the possible methods for fostering PEBs. However, previous studies have seldom discussed what type of information is most appropriate for the target behavior. Effective media through which to provide such information should be also discussed. In order to identify the most effective such information, as well as the effectiveness of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Declarative knowledge can ideally reduce uncertainty which allows people to take actions (Kaiser and Fuhrer, 2003). Moreover, Lee, Kurisu and Hanaki (2015) found that providing this kind of knowledge of the existing campaign could improve people‖s intention to perform the behavior.…”
Section: Information Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Declarative knowledge can ideally reduce uncertainty which allows people to take actions (Kaiser and Fuhrer, 2003). Moreover, Lee, Kurisu and Hanaki (2015) found that providing this kind of knowledge of the existing campaign could improve people‖s intention to perform the behavior.…”
Section: Information Provisionmentioning
confidence: 99%
“…It is also relevant when behavior is instrumental in optimizing a person‖s cost-benefit ratio (Kaiser and Fuhrer, 2003). For example, Fuel or CO 2 emission can be cut by switching from a gasoline-fueled car to a hybrid car, see Lee, Kurisu and Hanaki (2015) for example. Buying a fuel-efficient automobile has a greater impact on energy conservation than does curtailing driving behavior, see an example in (Stern and Gardner, 1981).…”
Section: Information Provisionmentioning
confidence: 99%